Building Anti-Corruption Awareness through Hebrews 13:5-6 Principles as an Ethical Measure to Prevent Corrupt Behavior - Umboh, Satria Evans; Lumintang, Marcellius; Tenda, Hapyvania (Sekolah Tinggi Teologi IKAT Jakarta, 2025)
This research focuses on corruption in every country, highlighting that it is unethical within the community, particularly for Christians involved in corrupt practices. Therefore, the researcher aims to provide solutions for fostering anti-corruption awareness and upholding ethical and theological principles as Christians. The principle the author presents is based on examining the meaning of Hebrews 13:5-6. The methodological approach employed in this study is grounded in the existing literature related to the problem topic. According to the results of this research, Christians who hold Christian values are more likely to avoid corrupt behavior. To promote anti-corruption awareness, we must follow the Hebrew principle of 13:5-6 as a guiding action against corruption. This research will provide a principle of education centered on God, which serves as the basis for ethical action, promoting awareness of anti-corruption and encouraging individuals to refrain from corrupt behavior.